ANALISIS RASIO LIKUIDITAS DAN RASIO SOLVABILITAS DALAM MENILAI KINERJA KEUANGAN PADA PT INDOFOOD SUKSES MAKMUR Tbk PERIODE 2013-2022 - Nurasri Ainnun, Ghea; Hermawan, Hengki (Journal of Research and Publication Innovation, 2024)
This research aims to find out how the financial performance of PT Indofood Sukses Makmur Tbk is based on cashmere financial performance analysis, liquidity ratios (current ratio, quick ratio, cash ratio) and solvency ratios (debt to assets ratio, debt to equity ratio, long term debt to equity ratio). The research method used is a quantitative descriptive method by comparing liquidity ratios and solvency ratios with Kasmir financial performance and collecting secondary data. The population of this research is the financial report of PT Indofood Sukses Makmur Tbk and the sample used in this research is the balance sheet and profit and loss report for 10 years from 2013-2022. The general analysis results based on financial ratios, namely liquidity position, can be seen that the calculation of the current ratio and quick ratio shows an unhealthy condition, namely the current ratio (CR) is 151%, where the industry standard is 200%, the quick ratio (QR) is 111% experienced unhealthy conditions where the industry standard value was 150% and the cash ratio (Cr) was 62% experienced healthy conditions where the industry standard value was 50%. The Solvency Ratio can be seen that for calculating the Debt to Asset Ratio (DAR) it shows an unhealthy condition, namely 49% or 0.49 and where the industry standard is 40%, the Debt to Equity Ratio (DER) shows an unhealthy condition, namely 98% or 0.98 where the industry standard is 90% and the Long Term Debt to Equity Ratio (LTDER) shows an unhealthy condition, namely 36% or 0.36 where the industry standard is 10%.